Value added products from urban organic wastes: a whole systems perspective. Issue 1 (May 2021) - Urbaniak, L; Sanchez, G; Lee, R; Satrio, J; Taylor, J; Spracklin, D
Abstract: Organic waste, specifically food waste and sewage sludge, is a challenge for sustainable waste management systems. The United States Environmental Protection Agency estimated that 38 million tons of food waste went to landfill in 2014. In the United States, public wastewater treatment plants process approximately 14 million dry tons of sewage sludge per year. Hydrothermal carbonization (HTC) is proposed as a solution to the large streams of food waste and sewage sludge. HTC is significantly more energy efficient than the industry standard processes used today. Compared to other biomass conversion processes, HTC has the highest carbon efficiency while having the lowest greenhouse gas emissions rate. HTC is a thermochemical process that converts wet biomass to a coal-like product that can be used as a solid fuel source, for soil amendment, or as a base for advanced applications such as activated carbon. Villanova University, with SoMax BioEnergy, is researching HTC and activation techniques for upgrading sewage sludge and food waste to activated carbon. The focus of the study is to evaluate these wastes as feedstocks for HTC and the subsequent activation to determine if an activated carbon adsorbent can be produced that is comparable to commercially available activated carbon using a whole systems perspective. This is a novel look as it involves determining the impacts of the process from social, technical, environmental, economic, and political (STEEP) perspectives.